A New Mapania Species (Cyperaceae) from Sarawak, Malaysia - Shabdin, Zinnirah; kalu, Meekiong; Mohd Isa, Miraadila (Borneo Journal of Resource Science and Technology, 2016)
Mapania kadimiana Shabdin, Meekiong & Miraadila, a new species from Sarikei Division, Sarawak is described and illustrated. It possesses distinctly 3-ranked leaves with tightly imbricated leaf sheaths and distinctly dark chocolate brown which closely similar to M. spadicea Uittien. The new species however, is different by having 1-4 spikes in sessile terminal capitulum whereas M. spadicea always has solitary spikes. M. kadimiana occurs lithophytically on rock surface or in damp or wet places on slopes near streams. Recognition of M. kadimiana increased the total number of Mapania in Sarawak to 32 species.